The Impact of organizational resilience, business continuity planning, work scheduling processes, and strategic agility on balanced scorecard performance: a case of Kenya Airways - Kurgat, E. (Strathmore University, 2025)
This study investigated Kenya Airways’ post-pandemic recovery by examining the impact of organizational resilience, business continuity planning (BCP), adaptive work scheduling, and strategic agility on its Balanced Scorecard (BSC) performance. Against a backdrop of financial strain, operational disruptions, and structural inefficiencies, the study explored how targeted recovery strategies influenced key organizational dimensions: financial health, customer satisfaction, internal operations, and employee development. Guided by Dynamic Capabilities Theory, the study adopted a positivist research philosophy and employed a descriptive correlational design. Primary data were collected through structured questionnaires administered to 356 Kenya Airways employees using stratified random sampling. Data analysis involved descriptive statistics and Ordinary Least Squares (OLS) regression, supported by validity and reliability tests. The findings revealed statistically significant positive relationships between the four independent variables and BSC performance. Organizational resilience and strategic agility emerged as particularly strong predictors of performance, underscoring the value of internal adaptability and forward-looking strategy in turbulent environments. Key recommendations include: enhancing investment in agile scheduling systems to improve operational flexibility, institutionalizing business continuity frameworks across departments, and strengthening employee training programs to support resilience. The study also recommends that Kenya Airways and similar carriers in resource-constrained markets prioritize strategic partnerships to bolster competitive positioning. The study is limited by its exclusive focus on Kenya Airways and reliance on employee perceptions, which may not fully capture customer or financial data realities. Future research should consider multi-stakeholder perspectives and comparative studies across multiple airlines in the region to generalize findings more broadly.
Full- text thesis